Effects of Sodium Bicarbonate Induced Blood pH Change on Oxidant Status and Thromboplastic Activity of the Kidney and Lung - TUNALI AKBAY, T.; EMIROGLU, A.; GUL, N.; EREN, N.; YARAT, A. (Asian Journal of Chemistry, 2010)
Oral ingestion of sodium bicarbonate is used to neutralize the acid in digestion, to decrease dental plaque and to heal the bladder infections. Excessive bicarbonate ingestion places individuals at risk for a variety of metabolic dearrangements. Our aim was to determine if sodium bicarbonate induced blood pH change has any effects on oxidant status and thromboplastic activity of lung and kidney. In the present study, the effects of sodium bicarbonate induced blood pH change on oxidant status and thromboplastic activity of lung and kidney tissues were investigated. The results revealed that sodium bicarbonate administration significantly increased blood pH and bicarbonate level, decreased chloride level and pO2 (partial oxygen pressure) and did not significantly change sodium, potassium concentration and pCO2 (partial carbon dioxide pressure). Kidney thromboplastic activity significantly decreased following sodium bicarbonate administration, which shows the impaired hemostatic balance in the kidney tissue. Lung thromboplastic activity did not significantly changed. Sodium bicarbonate administration also did not cause any oxidative damage both on kidney and lung. It seems likely that eight weeks oral sodium bicarbonate administration caused mild alkalosis and did not change oxidative status both on kidney and lung tissues but it impaired the hemostatic balance at kidney which can cause uncontrolled bleeding after any kidney damage.